From barriers to solutions: Advancing circular construction for sustainable growth - Chengxu, Gan; Hamedani, Sharareh Shahidi; Aslam, Sarfraz; Nan, Li (International Journal of Innovative Research and Scientific Studies, 2025)
China’s construction sector has become a key area for national sustainable development reforms, one of the largest and most resource-intensive industries globally. Despite the government’s initiative to introduce multiple circular construction-related policies, significant challenges remain in areas such as fragmented standards, weak regulatory mechanisms, and the absence of end-to-end tracking. This study aims to evaluate the implementation performance of China’s circular construction policies, identify core obstacles in institutional operations, and draw on governance experiences from European countries to propose feasible recommendations for institutional optimization. A qualitative research method was employed, including targeted content analysis of policy documents and comparative case studies of three pilot cities in China, to comprehensively assess the operational status of policies. Despite ongoing improvements to the policy framework, implementation challenges persist, including inconsistent standards, insufficient enforcement mechanisms, and weak integration of life-cycle concepts. Recommendations include incorporating life-cycle assessment tools into mandatory policy frameworks, establishing a unified building data platform, enhancing extended producer responsibility mechanisms, and driving the transformation of China’s construction industry toward a more resilient and internationally aligned circular system.